Сатира и юмор в народных книгах В. И. Даля - Юган, Н. Л.; Yugan, N. L. (Волинськиий національний університет імені Лесі Українки, 2012)
В статье представлены исследования в области комедийной поэтики сборников В. И. Даля «Солдатские досуги», «Матросские досуги», «Два сорока бывальщинок для крестьян». Здесь выявляются фольклорные и литературные источники комизма, проводятся параллели между далевскими сюжетами и пословичным, сказочным материалом. Писатель прибегает к комическому изображению жизненных событий для показания неприемлемости некоторых стереотипов поведения, просвещения и лёгкого усвоения информации военно¬служащими.The article presents a study of comic poetry collections by Vladimir Dal’ «Soldiers’ spare time», «Sailors’ spare time» and the series «The two forty stories for peasante». It identifies folklore and literature of comedy, and draws a parallel with proverbs and fairy-tale material. The writer uses the comic to events for the image reading unacceptability of certain stereotypes, educating and easy assimilatijn of information by military personnel.
Satire and Humor in V. I. Dahl’s Popular Books
Keywords: сатира; гумор; фольклор; публіцистика; народні книги; виховання; satire; humor; folklore; journalism; popular books; pedagogical